KOMPONEN PEMBELAJARAN DALAM AL-QUR’AN DAN HADIS - Jamila, Siti Hesniyatul (ILJ: Islamic Learning Journal, 2023)
he discussion in this paper is to describe the components of learning in the Qur'an and Hadith. The research methodology in this paper uses a qualitative approach with typeslibrary research. The data sources are scientific texts which are analyzed using content analysis. The findings of this study are(a). Educational goals or learning goals : QS. Al-Mujadilah verse 11 and QS. Al-Baqarah: 132.(b). Educators and students : QS. Al-Baqarah: 31-32 dan 129, QS. Al-Alaq: 1-5. QS. Ali Imron: 164, QS. Al-Jumu'ah: 2. Q.S. Lukman (31): 12-19(c). Material or curriculum : QS. Al-Kahfi: 10 years ago. Lukman: 27. (d). Learning methods : story method, QS. Thaha: 99.Amtsal (parable), QS. Al-Baqarah: verse 17 and QS. al-`Ankabut: 41.Abraham-Mauizhah (advice), QS. Joseph: 111,Targhib-Tarhib (reward and funishment), QS. Ar-Ra`du: Hiwar (dialogue), The type of hiwar is hiwar khitabi orta`abudi, hiwar washfi, dalam QS. al-Shaffat: 20-23, hiwarqishashi, hiwarjadali for example in surah al-Najm verses 1-5, the uswatun hasanah method in HR. Muslim.(and). Evaluation : QS. QS. Al-Baqarah: 155, QS. An-Name: 40, QS. An-Name: 27 in QS. Ash-Shaffat: 103, 106, dan 107.(f). Learning Media audio, from antaranya QS. al-‘Alaq (96); 1, QS.Al-Isra’ (17): 14, QS.Al-Ankabut (29): 45, QS.Al-Muzammil (73); 20. QS. Al-An'am (6); 97 dan 165, QS. At-Taubah (9); 11.QS. Al-Baqarah (2); 76, in QS. Yusuf (12); 5.Learning Media visual : QS. Al-Baqarah (2) 31 and the forerunner to the use of technology in learning is disclosed in QS. An-Naml: 29-30 and QS. an-Naml: 44, which is about the story of the prophet Solomon and Queen Balqis. Hadith about the visual learning media used by Rasulullah SAW in learning, namely forming a circle (HR. Bukhari). Directing his finger to the mouth (HR. Bukhari). Clench hands (HR. Bukhari). Hand gestures (HR. Tirmidhi). Chest gesture (HR. Bukhari). Using pictures (HR. Imam Bukhari) Using fingers (HR. Imam Muslim) and using gravel (HR. At-Tirmidhi).(g). Learning facilities or educational facilities found in QS. An-Nahl: 78, QS. Al-Mulk: 23 and QS. As-Sajdah: 9 and QS. A-Ballad : 8-9.